course Mth 174
W鲩ð~䈅ǵassignment #015
Question:
Question: Query 10.4.8 (was 10.4.1 3d edition formerly p. 487 problem 6) magnitude of error in estimating .5^(1/3) with a third-degree Taylor polynomial about 0.
Your solution:
Confidence Assessment:
Given Solution:
Given Solution: ** The maximum possible error of the degree-3 Taylor polynomial is based on the fourth derivative and is equal to the maximum possible magnitude of the n = 4 term of the Taylor series.
The present function is x^(1/3). Its derivatives are
All these derivatives are undefined at x = 0.
Since all the derivatives are easily evaluated at x = 1, we expand about x = 1.
The maximum possible magnitude of the fourth derivative f''''(x) = -80/81 x^(-11/3) between x = .5 and x = 1 occurs at x = .5, where we obtain | f '''' (x) | = 80/81 * (.5^-(11/3) ) = 12.54 approx. We will still have a valid limit on the error if we use the slight overestimate M = 13.
So the maximum possible error is | 13 / 4! * (.5 - 1)^4 |, or about .034.
.................................................
Self-critique (if necessary):
Self-critique Rating:
Question:
Question: Query 10.4.20 (was 10.4.16 3d edition) (was p. 487 problem 12) Taylor series of sin(x) converges to sin(x) for all x (note change from cos(x) in previous edition)
explain how you proved the result.
Your solution:
Confidence Assessment:
Given Solution:
** For even values of n the nth derivative is sin(x); when expanding about 0 this will result in terms of the form 0 * x^n / n!, or just 0.
If n is odd, the nth derivative is +- cos(x). Expanding about 0 this derivative has magnitude 1 for all n. So the nth term, for n odd, is just 1 / n! * x^n.
None of the Taylor coefficients exceeds the maximum magnitude M = 1.
For any x, lim(n -> infinity} (x^n / n!) = 0:
Putting this together formally in terms of the definition of the error term.
It's not obvious that x^(n + 1)/ (n + 1)! approaches zero for any x. If x
gets large, x^(n+1) gets very, very large.
However a ratio test will show that x^(n+1) / (n+1)! does approach zero
for any value of x, giving us the stated result.
The series does converge for all values of x.**
.................................................
Self-critique (if necessary):
Self-critique Rating:
Question:
Question: Query problem 10.3.10 (3d edition 10.3.12) (was 9.3.12) series for `sqrt(1+sin(`theta))
what are the first four nonzero terms of the series?
Your solution:
Confidence Assessment:
Given Solution:
We substitute the Taylor expansion of sin(x) into the Taylor expansion of 1 / sqrt(x) and ignore terms with powers exceeding 4:
Expanding y = sqrt(x) about x = 1 we get derivatives
y ' = 1/2 x^(-1/2)
y '' = -1/4 x^(-3/2)
y ''' = 3/8 x^(-5/2)
y '''' = -5/16 x^(-7/2).
Substituting 1 we get values 1, 1/2, -1/4, 3/8, -5/16.
The degree-4 Taylor polynomial is therefore
sqrt(x) = 1 + 1/2 (x-1) - 1/4 (x-1)^2 / 2 + 3/8 (x-1)^3/3! - 5/16 (x-1)^4 / 4!.
It follows that the polynomial for sqrt(1 + x) is
sqrt( 1 + x ) = 1 + 1/2 ( 1 + x - 1) - 1/4 (1 + x-1)^2 / 2 + 3/8 (1 + x-1)^3/3! - 5/16 (1 + x-1)^4 / 4!
= 1 + 1/2 (x) - 1/4 (x)^2 / 2 + 3/8 (x)^3/3! - 5/16 (x)^4 / 4!.
Now the first four nonzeo terms of the expansion of sin(theta) give us the polynomial
sin(theta) = theta-theta^3/3!+theta^5/5!-theta^7/7!.
We note that since sin(theta) contains theta as a term, the first four powers of sin(theta) will contain theta, theta^2, theta^3 and theta^4, so our expansion will ultimately contain these powers of theta.
We will expand the expressions for sin^2(theta), sin^3(theta) and sin^4(theta), but since we are looking for only the first four nonzero terms of the expansion we will not include powers of theta which exceed 4:
sin^2(theta) = (theta-theta^3/3!+theta^5/5!-theta^7/7!)^2 = theta^2 - 2 theta^4 / 3! + powers of theta exceeding 4
sin^3(theta) = (theta-theta^3/3!+theta^5/5!-theta^7/7!)^3 = theta^3 + powers of theta exceeding 4
sin^4(theta) = (theta-theta^3/3!+theta^5/5!-theta^7/7!)^4 = theta^4 + powers of theta exceeding 4
Substituting sin(theta) for x in the expansion of sqrt(1 + x) we obtain
sqrt(1 + sin(theta)) = 1 + 1/2 (sin(theta)) - 1/4 (sin(theta))^2 / 2 + 3/8 (sin(theta))^3/3! - 5/16 (sin(theta))^4 / 4!
= 1 + 1/2 (theta-theta^3/3! + powers of theta exceeding 4) - 1/4 (theta^2 - 2 theta^4 / 3! + powers of theta exceeding 4)/2 + 3/8 ( theta^3 + powers of theta exceeding 4) / 3! - 5/16 (theta^4 + powers of theta exceeding 4)/4!
= 1 + 1/2 theta - 1/4 theta^2/2 - 1/2 theta^3 / 3! + 3/8 theta^3 / 3! + 2 / ( 4 * 3! * 2) theta ^4 - 5/16 theta^4 / 4!
= 1 + 1/2 theta - 1/8 theta^2 + 1/16 theta^3 - 5/128 theta^4.
STUDENT SOLUTION:
Rewrite as sqrt (1+sin theta) = (1+sin theta)^(1/2)
Produce Taylor series for (1+x)^(1/2) using binomial expansion with p = 1/2:
(1+x)^(1/2) = 1 + x/2 + [(.5)(.5-1)x^2]/2! + [(.5)(.5-1)(.5-2)x^3]/3! ...
= 1 + x/2 + x^2/8 + x^3/16 ...
Produce Taylor series for sin theta
sin theta = theta - theta^3/3! + theta^5/5! - theta^7/7! ...
Substitute sin theta for x in series for (1+x)^(1/2):
sqrt (1+ sin theta) = 1 + (1/2)(theta - theta^3/3! + theta^5/5! - theta^7/7! ...) - (1/8)(theta - theta^3/3! + theta^5/5! - theta^7/7! ...)^2 + (1/16)(theta - theta^3/3! + theta^5/5! - theta^7/7! ...)^3 ...
sqrt (1+ sin theta) = 1 + theta/2 - (theta^2)/8 - (theta^3)/48 ...
What is the Taylor series for `sqrt(z)?
RESPONSE -->
Using f(x) = sqrt (z) will not work because f(0) and all derivatives of f(x) evaluated at 0 = 0.
Let f(x) = sqrt (1+x)
Using binomial expansion:
sqrt (1+x) = 1 + x/2 - x^2/8 + x^3/16 + ...
Substituting z-1 for x (since 1 + (z-1) = z)
sqrt (z) = 1 + (z-1)/2 - (z-1)^2/8 + (z-1)^3/16 + ...
What is the Taylor series for 1+sin(`theta)?
......!!!!!!!!...................................
RESPONSE -->
Since 1 is a constant, its Taylor series is itself (if f(x) =1, f(0) =1 and all derivatives of f(x) = 0
Taylor series for sin (theta) = theta - theta^3/3! + theta^5/5! - theta^7/7! + ,,,
Adding the two series gives
1 + sin (theta) = 1 + (theta - theta^3/3! + theta^5/5! - theta^7/7! + ,,,
= 1 + theta - theta^3/3! + theta^5/5! - theta^7/7! + ,,,
How are the two series combined to obtain the desired series?
......!!!!!!!!...................................
RESPONSE -->
See previous response. Since a Taylor series is a power series it follows the rules of a power series, including the rule that power series can be added term by term.
.................................................
......!!!!!!!!...................................
STUDENT COMMENT:
The Taylor series for sqrt(z) provides an interesting way to manually calculate approximations of square roots.
.................................................
"
Self-critique (if necessary):
Self-critique Rating: